Evaluation of cardiopulmonary function and health outcomes among petrol pump attendants in Lucknow district - Singh, Hari; Singh, Seema; Raza, Syed T. (International Journal of Research in Medical Sciences, 2024)
Background: Petrol pump attendants face heightened health risks due to prolonged exposure to gasoline fumes, which contain harmful chemicals like benzene and particulate matter. This community is generally neglected regarding their health. This study investigates the impact of such occupational exposure on the lung and cardiovascular functions of petrol pump workers in Lucknow, India. Methods: A case-control study of 80 petrol pump workers and 80 healthy controls in Lucknow measured physical and physiological parameters, including systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), mean arterial pressure (MAP), pulse rate, and peak expiratory flow rate (PEFR). Analysis utilized independent t-tests and receiver operating characteristic (ROC) curve analysis. Results: Petrol pump workers exhibited significantly higher SBP (126.7 mmHg versus 113.2 mmHg, p<0.001), DBP (81.2 mmHg versus 72.3 mmHg, p<0.001), PP (45.4 mmHg versus 41.0 mmHg, p=0.007), MAP (96.1 mmHg versus 85.3 mmHg, p<0.001), and pulse rate (85.4 bpm versus 72.5 bpm, p<0.001) compared to controls. PEFR was significantly lower in petrol pump workers (365.3 l/min versus 478.9 l/min, p<0.001), indicating reduced lung function. ROC curve analysis demonstrated high diagnostic accuracy for PEFR (AUC=0.84) and pulse rate (AUC=0.88) in distinguishing between cases and controls. Conclusions: Petrol pump workers in Lucknow exhibit significantly impaired lung function and elevated cardiovascular parameters, likely due to prolonged exposure to gasoline fumes. These findings underscore the need for improved protective measures and health monitoring for this occupational group.